MANIFESTATION OF GOOD GOVERNANCE PRINCIPLES IN PASSPORT SERVICES AT THE CLASS I IMMIGRATION OFFICE OF TPI BANDUNG - Atmadja, Erlangga; Pujonggo, Seno Setyo; Jani, Salsabila Andi (Qawwam : The Leader's Writing, 2025)
The effectiveness of passport services serves as a fundamental benchmark for assessing the quality of bureaucracy and a nation's progress in public administration. To improve the quality of immigration services, the application of good governance principles—encompassing transparency, accountability, participation, and efficiency—plays a pivotal role. This study aims to analyze the manifestation of good governance principles in the provision of passport services at the Class I TPI Bandung Immigration Office. Through a qualitative case study approach, this study thoroughly examines how each of these principles is implemented in operational procedures, from the application stage to the issuance of the passport. The analysis focuses on identifying successes, challenges, and the public's perception of the current implementation. The findings are expected to provide a comprehensive overview of the synergy between good governance and the quality of public services in the immigration sector, as well as to formulate strategic recommendations for stakeholders to optimize services, enhance public satisfaction, and strengthen the nation's competitiveness.